영상콘텐츠에서 테마공간으로의 전환 양상:각색을 통한 재현을 중심으로 - 신동희; 김희경; Shin, Dong-Hee; Kim, Hee-Kyung (한국콘텐츠학회 논문지, 12(4), 2012)
The purpose of the thesis is to answer the question on how the visual image content, being the original content, should be adapted to and represented as a spatial content. The thesis focuses on adaptation as the key in the conversion process of visual image content to a themed space. There are many published studies dealing with storytelling, adaptation from books to movies and TV shows, or from movies to games and vice versa. On the contrary, when it comes to adaptation from visual image content to spatial content, noticeably few studies were done on the method, and fewer studies view adaptation as the prior step of storytelling. This study first defines adaptation, and then applies the methods of Gianetty and Dudley which is further incorporated into the conversion of visual image content into a themed space. It then turns the attention to the characteristics of themed spaces. A case study highlights that a themed space is a spatial representation of the story, image and action in the visual image content, and analyze the type of adaptation made. The study results draws two conclusions; adaptation must be carried out prior to the storytelling of the spatial content; and opposed to a third-person view of the visual image content, the main factor in a themed space is first-hand experience. Thus, the thesis suggests that conversion from visual image content to themed spaces are not merely imitative but is a full range of recreation of a new content. It is expected that more detailed analyses on the particulars will lead to feasible outcome on implementing various methods of adaptation and bring about effective conversions between the visual image contents and themed spaces. 본 논문은 영상콘텐츠에서 공간콘텐츠로의 전환의 핵심을 각색(adaptation)에 두고, 테마공간의 원형콘텐츠인 영상콘텐츠가 어떻게 각색되어 공간으로 재현되어야 하는가를 밝히는 것을 목적으로 한다. 또한 스토리텔링에 대한 연구는 무수히 많이 쏟아져 나오고 있고, 소설의 영화화나 TV드라마화, 영화의 게임화나 그 반대와 관련한 각색 연구는 많지만 영상콘텐츠에서 테마공간으로 전환 시의 각색의 방법과 스토리텔링의 전단계라는 측면에서의 각색에 대한 연구는 부족한 편이다. 우선 각색의 정의를 내리고, 자네티와 더들리의 각색방법을 차용하여 영상콘텐츠의 테마공간화에 적용해 보았다. 이어서 테마공간의 특징을 살펴본 후 테마공간은 결국 영상콘텐츠의 이야기 이미지 행위의 재현 장소임을 사례분석과 함께 밝히고, 각각 어떤 각색을 통해 재현되고 있는가를 분석하였다. 연구결과 공간의 스토리텔링보다 각색이 선행작업이어야 하고, 3인칭 시점의 영상콘텐츠와는 달리 1인칭 시점의 테마공간 재현의 핵심은 관람이 아닌 체험임을 확인하였다. 따라서 본 논문에서는 영상콘텐츠에서 테마공간의 전환은 단순한 모방이 아니라 새로운 콘텐츠로 재창조되었음을 밝혔다. 향후 다양한 테마공간의 구체적인 각론적 층위에서의 분석을 통해 양자간의 전환이 효과적으로 작용하고, 다양한 각색 방법이 실질적으로 적용되기를 기대한다.